1
$\begingroup$

While reading through my textbook, I came across this particular equation: $$ x = x\log (y) + \log (y) $$ But they solve it by doing this: $$ x = x\log (y) + \log (y) $$ $$ x = (x + 1)\log(y) $$ $$ \frac {x}{x+1} = \log(y) $$ $$ y = 10^{\frac{x}{x+1}} $$ Which is fine, but I don't understand why they didn't do it like this: $$ x = x\log (y) + \log (y) $$ $$ x=\log(y^x)+\log(y) $$ $$ x=\log(y^{2x}) $$ $$ x=2x\log(y) $$ $$ \frac{x}{2x}=\log(y) $$ $$ y=10^{\frac{x}{2x}} $$ I'm confused over which one is correct.

$\endgroup$
1
  • $\begingroup$ Yep, I feel like an idiot! Thanks, shost71 and MPW! $\endgroup$
    – dr_nefario
    Mar 16, 2015 at 2:34

3 Answers 3

1
$\begingroup$

I think you have got an error: $ x = log(y^x) + log(y) = log(y^x\cdot y) = log(y^{x+1})$

$\endgroup$
0
$\begingroup$

You've made an error.

$\log y^x +\log y$ is $\log y^{x+1}$, not $\log y^{2x}$

$\endgroup$
0
$\begingroup$

When you do $$ log(y^x) + log(y) $$ this equals: $$ log(y^x \cdot y) = log(y^{x+1}) $$

which gives $ y = 10^{\frac{x}{x+1}} $

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.